The Implementation of Office Management in Improving the Work Effectiveness of Employees at the Perkim Office, Bolsel Regency - Meita As. Thanta (Atha Publishing Globalindo, 2026)
This research is entitled The Application of Office Management in Improving the Work Effectiveness of Employees at the Perkim Office, Bolsel Regency. This study aims to find out the application of office management in increasing the work effectiveness of employees in the Perkim Office, Bolsel Regency and to find out what factors most affect the work effectiveness of employees in the Perkimtan Office, Bolsel Regency. This study uses qualitative research methods. The results of this study show that there is office management in the Perkimtan Office, namely: Office management in documents and archives; Office management in administrative procedures; and Office Management in human resources/employees. Then in improving the effectiveness of employee work at the Housing, Settlement and Land Office, there are several roles, namelythe role of planning is carried out, namely through the preparation of work programs, the preparation of work plans and the preparation of strategic plans. The role of the organizer is to give tasks and responsibilities to subordinates. The role of the briefing is to provide work instructions through weekly meetings. And the role of supervision is by evaluating work in the office and in the field. And there are three factors that have the most influence on the effectiveness of employees' work, namely motivation, job satisfaction anddiscipline.